ANALISIS PERLAKUAN AKUNTANSI ASET TETAP BERDASARKAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 16 TENTANG ASET TETAP PADA PT. PERKEBUNAN NUSANTARA I (PERSERO) LANGSA - Inge Tasya Lonita; Afrah Junita; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
The research was conducted with the aim of knowing the accounting treatment of assets in accordance with PSAK No. 16, with the suitability of accounting for fixed assets at PT. Perkebunan Nusantara I (PERSERO) Langsa. The type of research used is qualitative. Sources of data used are primary and secondary data, and data collection methods obtained by using library research methods, interview methods, and documentation methods. The data analysis method used is a comparative descriptive analysis method. The results of this study indicate that in carrying out the accounting treatment of fixed assets PT. Perkebunan Nusantara I (PERSERO) Langsa it is not in accordance with from PSAK No. 16. The discrepancy regarding: the grouping of immature plantations (TBM) into fixed assets resulted in the value of fixed assets is not fair at PT. Perkebunan Nusantara I (PERSERO) Langsa. In addition, that causes the financial statements to be less reliable and relevant. The limitation of this study is that the authors only take to indicators of fixed asset accounting treatment, namely recognition and depreciation only. Given these limitations, the researches provides suggestions to further researches to expand research by adding indicators of fixed asset accounting measures such as measurement and disclosure.